Analysis of Sanitation, Internal and External Factors Affecting Stunting Knowledge among At-Risk Communities in Central Sulawesi, Indonesia - Syukur, Djunaedil; Ganing, Abdul; Arsyad, Gusman; Mustaqim, Udin (Jurnal Kesehatan Manarang, 2025)
Stunting remains a significant public health challenge in Indonesia, particularly in underdeveloped regions like Central Sulawesi, where limited access to health information and services contributes to poor nutritional outcomes. This study evaluates the effectiveness of interventions in improving knowledge about stunting among four vulnerable groups: families with stunted children, pregnant women, couples of childbearing age (PUS), and female senior high school students in Central Sulawesi. Using a pre-and post-test design, the average knowledge scores on stunting increased from 14.12 to 50.95 among pregnant women, 28.57 to 58.43 among PUS, and 34.82 to 57.67 among female senior high school students. Correlation analysis revealed that sanitation, internal, and external factors were strongly associated with knowledge improvement (correlation values between 0.05% and 0.01%). These findings suggest that tailored, community-based educational approaches can significantly enhance awareness and knowledge of stunting, thereby contributing to long-term prevention efforts in underdeveloped regions.